Ibogaine (iboga tabernanthe) as a potential anti-addictive treatment in the pipeline : a short communication - Mohamed Nazar, Nor Ilyani (2014)

(untitled)
Opioid addiction is still an emerging problem worlwide. In this South East Asia region, particularly Malaysia, opioid is identified as the main substance of dependency. Due to its nestled relationship between Intravascular opiod usage and the seroprevalence of Human Immunodeficiency Virus (HIV) in the population, the Malaysian government has adopted methadone maintenance therapy (MMT) as one of the harm reduction approaches in curbing the problem. Despite evidents of succes, methadone therapy has shown variabilities in terms of results and clinical outcomes which is very much dose and adherence dependence. This has no doubt suggesting for further research and development of anti-addiction treatment. Ibogaine on the other hand is far left behind from the streamline treatment of substance addiction though studies keep on showing auspicious results on the clinical use. Ibogaine or the name Iboga tabernanthe is one of the African shrubs which is used in ritual of African Bwiti Community. Due to its pharmacological properties, it is classified as psychedelic and has been used in various countries (Canada, New Zealand, Australia and Africa) to treat drug addiction. Pharmacologically, Ibogaine was found to exert its effects at various neurological systems including dopaminergic, glutamatergic, serotonergic, nicotinic and colinergic pathway as well as receptors including opioid, sigma and neurotransmitters such as gamma amino butyric acid (GABA). The mechanism of action is through its active metabolites of noribogaine which may act as addiction interrupter. With long half life, it will sustain in the blood concentration and prolong the pharmacological effects. In the case of opioid addiction, ibogaine exhibits the ability to reduce extracellular level of dopamine in the nucleus accumbens and further, its effects on dopaminergic function are largely regulated by its interaction with serotonin receptors. Physical side effects include QT prolongation, ataxia, dystonia, nausea, vomiting and light sensitivity. Various clinical and animal studies have been conducted worlwide with promising results. This paper will review the feasible evidence of clinical application.